2004
DOI: 10.1089/vbz.2004.4.360
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of West Nile Virus in Connecticut: A Five-Year Analysis of Mosquito Data 1999–2003

Abstract: Two hundred and ten isolations of West Nile virus (WNV) were obtained from 17 mosquito species in six genera in statewide surveillance conducted in Connecticut from June through October, 1999-2003. Culex pipiens (86), Culex salinarius (32), Culex restuans (26), Culiseta melanura (32), and Aedes vexans (12) were implicated as the most likely vectors of WNV in the region based on virus isolation data. Culex pipiens was abundant from July through September and is likely involved in early season enzootic transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
206
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 249 publications
(222 citation statements)
references
References 38 publications
16
206
0
Order By: Relevance
“…pipiens in surveillance activities conducted over the last 6 years ( 6 , 10 , 14 , 15 ) clearly incriminates this species as the predominant mosquito vector in this region. However, while enzootic transmission to birds is strongly supported by a number of host-preference studies on regional populations ( 8 , 9 , 16 – 18 ), no consensus has been reached on the role of Cx.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…pipiens in surveillance activities conducted over the last 6 years ( 6 , 10 , 14 , 15 ) clearly incriminates this species as the predominant mosquito vector in this region. However, while enzootic transmission to birds is strongly supported by a number of host-preference studies on regional populations ( 8 , 9 , 16 – 18 ), no consensus has been reached on the role of Cx.…”
Section: Discussionmentioning
confidence: 95%
“…This interpretation was viewed as consistent with the incidence of human cases in 3 densely populated urban areas of Connecticut in 2002, where most viral isolations (78%) were from Cx. pipiens ( 6 ). Kilpatrick et al ( 7 ), integrating WNV testing data from New York from 2000 to 2003 with information on mosquito abundance, infection prevalence, vector competence, and biting behavior, further suggested that Cx.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations